ASSESSMENT OF HEAVY METAL CONCENTRATION IN MARINE SEDIMENTS IN TERENGGANU WATERS - HING, YIP TAIM; EVONNE, TAN; HAN, POONG JUN; SHENG, TEE LIAN; RAMLI, MUHAMMAD HASBI; SABUTI, ASNOR AZRIN; CHUAN, ONG MENG (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2021)
The distribution of heavy metals (Cu, Zn, Cd, Pb) in surface sediments was examined in waters off the coast of Marang, Terengganu. A total of 20 samples were collected using Ponar grab and analysed by inductively coupled plasma-mass spectrometer after closed digestion with acid. The sediments were filtered using a dry sieving method to determine their particle size. The spatial distribution maps on the concentration of selected metals were drawn using the ArcGIS software. Results showed that the average concentration of Cu, Zn, Cd, and Pb were 2.33±0.38 μg/g dry weight, 28.4±3.78 μg/g dry weight, 0.09±0.01 μg/g dry weight and 8.35±1.48 μg/g dry weight, respectively. The level of pollution was also evaluated using the Index of Geoaccumulation (Igeo) and Pollution Load Index (PLI). All Igeo and PLI values obtained were low, which indicated low or no pollution. Meanwhile, the sediment mean size ranged between -0.77Ø and 3.18Ø, which characterised a sandy type of sediment. Correlation analysis showed a positive correlation between the heavy metals and sediment size. The results indicated that there was a common source of heavy metal pollution in the study area, possibly from shipping activities. Overall, there was no significant heavy metal pollution in the waters off Marang. This finding is important as the data could be used to evaluate the risk of metal contamination and the impact of anthropogenic activities on the marine environment.